Developing cholinergic basal forebrain neurons are sensitive to thyroid hormone - Gould, E (J Neurosci, 1989)
The influence of thyroid hormone on the development of cholinergic neurons in nucleus basalis was assessed in hyperthyroid, hypothyroid, and euthyroid rats by use of CAT immunohistochemistry and single- section Golgi-impregnation histology. Animals were made either hyperthyroid by daily injections of 1.0 micrograms/gm body weight triiodothyronine starting at postnatal day (P) 3 or hypothyroid by providing 0.4% propylthiouracil in the diet of dams from P2. Compared to developing control rats, increased exposure to thyroid hormone resulted in accelerated expression of CAT in nucleus basalis neurons. Overshoot in cell body size, a normal developmental phenomenon of cholinergic neurons in the basal nuclear complex, occurred earlier in hyperthyroid brains and was of a greater magnitude than in controls. Furthermore, increased numbers of primary dendrites and dendritic branchpoints accompanied by dendritic and perisomal filopodia-like structures were observed for nucleus basalis neurons in hyperthyroid rats. These dendritic changes persisted throughout the second postnatal month. After the fifth postnatal week, cell body sizes of these hyperthyroid CAT-positive neurons began to decrease and by P50 were significantly less than controls or similarly treated animals at earlier ages. By P64, the number of cholinergic neurons in nucleus basalis was appreciably less than in age-matched controls. Hypothyroidism resulted in a delay of normal CAT expression that persisted throughout the third postnatal week. After this time, CAT staining increased until normal immunoreactivity was attained in cell bodies, fibers, and terminal regions by P35. A deficit in thyroid hormone during development prevented overshoot in perikaryal size and resulted in diminished cross-sectional areas throughout the cholinergic nucleus basalis at all ages examined. Hypothyroidism also prevented the normal overproduction of dendrites in those cells and produced stunted dendritic trees at all ages examined. These morphological abnormalities persisted throughout the second postnatal month. The effects of thyroid hormone on cholinergic projection neurons in the rat brain appeared relatively selective for cells in the basal nuclear complex because neither hypothyroid nor hyperthyroid treatment produced changes in the cell body areas of the phenotypically similar CAT-positive neurons of the pontomesencephalotegmental complex.(ABSTRACT TRUNCATED AT 400 WORDS)